Drug delivery engineering principles for drug therapy - Saltzman, W. Mark (Topics in chemical engineering (Oxford University Press), 2001)
This text is a synthesis of the principles that govern rates of drug transport, reaction, and disappearance in physiological and pathological situations, providing a working foundation for those in the field of drug delivery. The book covers advanced drug delivery and contemporary biomaterials.